Evaluation of the Swimming Achievement Coaching Program of the Sriwijaya State Sports School South Sumatera Province - M. Haris Satria; Rendy Septiano; Martinus (UNIB Press, 2023)
This study aims to evaluate swimming coaching in SONS using the CIPP evaluation model. Data were collected through observation, interviews, and documentation. The data obtained are analyzed qualitatively by steps, data reduction, data presentation, and drawing conclusions. This study concludes: 1) the evaluation of the context of the implementation of coaching has not been directed and does not have planning guidelines must be improved as early as possible, 2) Evaluation of inputs in the selection process of coaches, athletes, infrastructure and funding is still not effective, 3) evaluation process consisting of training programs, competitions, health of athletes and coaches and coordination has not run optimally, 4) evaluation of SONS coaching products from the aspect of medal achievement can be assumed to have not been successful. Furthermore, an assessment and determination of each component is evaluated. The results of the analysis and determination of decisions are then used as a basis for improving each program and improving and providing decisions, researchers provide recommendations to SONS stakeholders so that they are directed to plan coaching to excel in the future.